Conductometric determination of propranolol hydrochloride in pharmaceuticals - Sartori, Elen Romão; Barbosa, Nathália Vieira; Faria, Ronaldo Censi; Fatibello-Filho, Orlando (Eclética Química, 2011)
In this paper the conductometric titration of propranolol hydrochloride in pharmaceutical formulations using silver nitrate as titrant is proposed. The method was based on the formation of an insoluble salt (AgCl(s)) between the chloride of propranolol hydrochloride molecule and Ag(I) ions of the titrant AgNO3. The effect of the PROP-AgNO3 concentrations and the interval of time between the successive additions of the titrant on the shape of the titration curve were studied. The obtained recoveries for four samples ranged from 96.8 to 105%. The proposed method was successfully applied in the determination of propranolol hydrochloride in several pharmaceutical formulations, with results in close agreement at a 95 % confidence level with those obtained using official spectrophotometric method.